Risk Attitudes Across The Life Course. (24th October 2017) - Dohmen, Thomas; Falk, Armin; Golsteyn, Bart H. H.; Huffman, David; Sunde, Uwe
Abstract : This article investigates how risk attitudes change over the life course. We study the age trajectory of risk attitudes all the way from early adulthood until old age, in large representative panel data sets from the Netherlands and Germany. Age patterns are generally difficult to identify separately from cohort or calendar period effects. We achieve identification by replacing calendar period indicators with controls for the specific underlying factors that may change risk attitudes across periods. The main result is that willingness to take risks decreases over the life course, linearly until approximately age 65 after which the slope becomes flatter.